Mutual Recognition Agreements: A Gateway to Global Opportunities or A Pathway of Challenges in Indonesian Economics for Halal Agri-Food Sector - Azizah, Hasnaa Nur; Ramadhan, Muhammad Arief; Utami, Tanaya Fauzia; Hidayati, Nurul; Casim, Rashdi M. (IPB University, 2025)
Indonesia, with the world's largest Muslim population, holds significant potential in the global Halal economy. The mandatory Halal certification in Indonesia presents both challenges and opportunities for international businesses. Mutual Recognition Agreements (MRAs) facilitate trade by enabling the acceptance of Halal certifications issued by recognized foreign bodies. While MRAs offer Indonesian businesses access to global markets, they also pose challenges such as increased competition from imported Halal products. This study explores the potential impacts of MRAs on the Indonesian Halal agri-food sector, analyzing the challenges and opportunities for local businesses. Key considerations include strengthening Halal standards, supporting SMEs through tailored financing schemes and government incentives, and ensuring the quality and authenticity of imported Halal products. The study emphasizes the need for a comprehensive strategy that balances market access with the protection of domestic producers while leveraging Indonesia's competitive advantages in the global Halal market.